IPadagogy: appropriating the iPad within pedagogical contexts. (1st January 2013) - Cochrane, Thomas; Narayan, Vickel; Oldfield, James
This paper critiques eight m-learning projects, including four m-learning projects using iPads in 2010 followed by a further four iPad projects in 2011. Using an action research methodology, the authors explore the impact of the integration of the m-learning projects on the pedagogical approaches of these courses. The eight iPad projects present different approaches to the integration of the iPad within a variety of educational contexts. The projects were informed by six critical success factors identified from thirty m-learning projects between 2006 and 2010, and illustrate the potential for the iPad to become a pedagogical game changer.